Point and Band Placement of Fertilizers for Higher Productivity and Profitability - Sonnad, Prakash; Singh, Teekam; Das, Tanmay (Chronicle of Bioresource Management, 2023)
Plants need minerals and nutrients for growth and development. They have to be applied to the crops at right time, right place, right rate and right sources (4Rs). To fulfil these ‘4R’ nutrient management stewardship, point and band placement of fertilizers are the best methods of fertilizer application to achieve higher productivity, profitability and nutrient use efficiencies. These are the potential techniques of fertilizer application over broadcasting of fertilizers in cereal crops like maize, rice and wheat. These simple techniques consume less fertilizers but give higher yield. Further, less weed infestation and loss of nutrients through volatilization, leaching and denitrification and fixation are additional advantages with point and band placement methods over broadcasting of fertilizers.